2019
DOI: 10.4103/psychiatry.indianjpsychiatry_443_18
|View full text |Cite
|
Sign up to set email alerts
|

Profile of students referred for the assessment of scholastic backwardness at a tertiary care center

Abstract: Background:Scholastic backwardness (SB) is a challenging problem affecting school-going children. Students seeking evaluation and certification of SB, especially in class nine and ten are on a rising trend in Kerala, the most literate state in India. However, there is a paucity of research regarding this.Objectives:The objectives of this study are to determine the clinical, sociodemographic, and academic profile of students referred with “difficulty in academics” in the psychiatry department of a government te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 7 publications
(6 reference statements)
0
9
1
Order By: Relevance
“…Outreach programs addressing the stigma of mental illness in communities and schools through the promotion of mental health, and programs with a view to reduce suicide rates have also been developed (Patel, Varma, Nimbalkar, Shah, & Phatak, 2020; Pathare et al, 2020; Ramadas & Vijayan, 2019; Shankar, Sievers, & Sharma, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Outreach programs addressing the stigma of mental illness in communities and schools through the promotion of mental health, and programs with a view to reduce suicide rates have also been developed (Patel, Varma, Nimbalkar, Shah, & Phatak, 2020; Pathare et al, 2020; Ramadas & Vijayan, 2019; Shankar, Sievers, & Sharma, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Students with intellectual disability, passing the exams scoring higher marks than the usual students is not uncommon. 7 In the quest of getting a centum pass in schools and the desire of parents to see their children passing 10 th standard by hook or by crook, an illogical and unscrupulous system thrives in Kerala. Do we need to be part of this system?…”
Section: From a Pedagogical Point Of View An Educationalmentioning
confidence: 99%
“…In a study conducted in a tertiary care centre in Kerala, it was found that majority of children who seek certification for scholastic backwardness was slow learners (IQ between 71 and 89). 7 Most of them(60%) were from high school and 80 % of the high school students were attending for their first ever assessment of SB. 7 Nevertheless, these children deserve attention and assistance, beginning from the early years.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The works of Kendil (2019) and Ramadas and Vijayan (2019) are devoted to the examining of various aspects of psychologists' professional activity. Kendil (2019) reveals the features of psychologist's work with victims of a terrorist attack.…”
mentioning
confidence: 99%